PENGARUH MODEL PROBLEM BASED LEARNING DENGAN PEMANFAATAN LINGKUNGAN DALAM MENINGKATKAN HASIL BELAJAR SISWA - Sirendeng, Siska; Mondolang, Aswin Hermanus; Mandang, Theresje (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aims to determine the effect of Problem Based Learning (PBL) with environmental utilization in improving student learning outcomes. The research method used is the experimental method, with the design, “One Group Pretest-Posttest” research. This research was conducted in three stages. The first stage is giving a pretest to measure students' initial abilities. The second stage is to provide treatment, namely Problem Based Learning with environmental utilization. And in the third stage, giving a posttest as an evaluation. The subjects of this study were X MIA 1 students of SMA Negeri 1 Tondano in the 2021/2022 school year. The results of data analysis obtained the average pretest score was 42.16 and the posttest score was 79.5. The results of hypothesis testing using the Paired Sample Test t-test obtained a sig. (2-tailed) of 0.000 <0.05. the data shows that there is an effect of the Problem Based Learning (PBL) model on Newton's material with environmental utilization on learning outcomes. It can be concluded that the Problem Based Learning (PBL) model with environmental utilization can improve student learning outcomes.